KRAS and SKIL mutations synergistically promote pancreatic tumorigenesis through the ubiquitin-proteasome-mediated degradation of Smad4 - Chenxi Wang; Yarui Ma; Haixia Cheng; Junhu Yuan; Yixuan Zhang; Mei Liu; Xiaobing Wang; Yuchen Jiao (Journal of Experimental & Clinical Cancer Research, 2026)
Abstract Background Pancreatic cancer development requires oncogenic KRAS plus additional genetic hits, yet these cooperating events remain poorly defined. Starting from a germline SKIL A512T mutation discovered in an infant with IPMN, we explored the synergistic role of SKIL and KRAS in tumorigenesis. Methods HEK293T cells with engineered SKIL A512T and/or KRAS G12V mutations were analyzed for proliferation, tumorigenicity, and signaling. Transcriptomics, ubiquitination assays, and protein interaction studies (Co-IP, immunofluorescence) delineated the mechanism. Results SKIL normally protects Smad4 by binding its MH2 domain; SKIL loss exposes this domain to ubiquitination, but degradation occurs only when KRAS mutation upregulates the E3 ligase SMURF2. Clinically, a significant positive correlation was observed between SKIL and Smad4 protein expression in KRAS -mutant IPMN tissues. Conclusion We identify a novel synergy between SKIL loss and KRAS activation that drives pancreatic tumorigenesis through targeted Smad4 degradation. This study aids in identifying high-risk populations for pancreatic cancer, specifically those harboring KRAS mutations.